AN UNUSUAL CASE OF SCHISTOSOMUS REFLEXUS WITH CYCLOPS IN A GOAT- A CASE REPORT - KANTHARAJ, S (The Indian Journal of Animal Reproduction, 2010)
A case of dystocia due to schistosomus retlexus with cyclops in a goat is reported.
Keywords: Dystocia; schistosomus reflexus; cyclops; goat